Review of Complexity perspectives on researching language learner and teacher psychology; Editors: Richard J. Sampson, Richard S. Pinner; Publisher: Multilingual Matters, 2021; ISBN: 9781788923545; Pages: 304 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2021)
One thing that immediately struck me when I sat down to write this piece was the realization that this is yet another review of a book devoted to the application of complex dynamic systems theory (CDST) to second and foreign language (L2) education. On the one hand, this might appear a little strange since I am certainly not an ardent believer in this theory and while I do recognize some of its merits, I have not used it as a theoretical framework in any of the studies I have conducted so far. On the other hand, though, the reason why I am attracted to publications on this topic could be that I am still waiting for someone to convince me that it is indeed the “silver bullet” that will not only help us disentangle the intricacies of L2 learning and teaching but also offer pedagogically sound insights that will contribute to more effective instruction. In fact, I finished my previous review of a recent book dealing with CDST-driven research methods in applied linguistics with the following comment: “I hope that Phil Hiver and Ali Al-Hoorie will continue their efforts to show the utility of CDST and perhaps one day they will also write a book about how adopting complexity theory can actually translate into more effective instruction in the language classroom” (Pawlak, 2020a, p. 394). As fate would have it, a different tandem of scholars has decided to confront this formidable challenge. Richard J. Samson and Richard S. Pinner state in the introduction to their edited volume: “We united under the motto complexity should be made simple [emphasis in original]. Our aim was to make complexity paradigms and research more accessible to people like ourselves, that is, practitioning language teachers who also engage in research” (p. 6). When going over the successive chapters included in this edited collection, I was constantly asking myself if the authors were succeeding in accomplishing this undoubtedly ambitious goal, and it is this vital issue that the review focuses on. Given the nature of the book and limitations of space, I am not going to describe in detail, let alone evaluate, each of the chapters. Rather, the comments are meant to refer to the entire publication, even though they might be illustrated by examples taken from specific papers.